4 - « Flamber moins et investir utile » : la promotion de l’entrepreneuriat chez des migrants de retour au Sénégal - Dimé, Mamadou (Africa Development, 2021)
The objective of this article is to provide an overview of the many investment initiatives put in place by returning migrants in Senegal. It is based on a series of qualitative data collected from returning migrants with diverse profiles (gender, skill level, ethnicity, brotherhood, years spent abroad, host countries, type of business, the experience of returning back home, etc.). The article starts by documenting the experience of the returning migrants, their motivations, their entrepreneurial vocation as well as the strategies involved in setting up their business concerns. The article also highlights the social, economic, cultural and institutional barriers to the implementation of the investment project. The article shows the manner in which the migration experience, the amount of resources (symbolic, material) and the new ethos of entrepreneurial values gained through migration are employed in the new vocation. Finally, suggestions are offered for an evaluation of the policies to support economic initiatives of migrants while bringing out a set of proposals put forward by the people we interviewed to mitigate the various challenges they are confronted with.